Rapid Responses of Winter Aphid-Parasitoid Communities to Climate Warming - Tougeron, Kévin; Damien, Maxime; Le Lann, Cécile; Brodeur, Jacques; van Baaren, Joan (Frontiers in Ecology and Evolution, 2018)
Consequences of environmental fluctuations, including those associated with climate changes, can have a knock-on effect from individual to community scale. In particular, changes in species seasonal phenology can modify the structure and composition of communities, with potential consequences on their functioning and the provision of ecosystem services. In mild climate areas, aphids can be present in cereal fields throughout the winter, which allows aphid parasitoids to remain active. Using a nine-year dataset of aphid-parasitoid winter trophic webs in cereal fields of Western France, we report that the community structure and composition that prevailed before 2011 have recently shifted toward a more diversified community, with the presence of two new braconid parasitoid species (Aphidius ervi and Aphidius avenae), a few hyperparasitoid species and one aphid species (Metopolophium dirhodum). Increases in minimal winter temperatures and the frequency of frost events across the years partially explain observed community changes. Strong bottom-up effects from the relative abundances of aphid species also determine the relative abundance of parasitoid species each winter. Strong compartmentalization in parasitoid preference for host is reported. We suggest the recent modifications in parasitoid community composition to be linked to shifts in diapause expression (reduction or arrest of the use of winter diapause) and to host availability throughout the year. We highlight the implications for natural biological control in cereal fields. Perspectives are proposed to predict the composition of future host-parasitoid communities in the climate change context.